New-Onset Anti-LGI1 Encephalitis in a Pregnant Woman - Britteny Randall; Eric Schmitt; Blaine McGraw; Donald Gloeb; Matthew Blattner (Reproductive Medicine)
Background and Clinical Significance: Anti-Leucine-rich glioma inactivated-1 (anti-LGI1) encephalitis is a rare, autoimmune disorder often presenting with limbic encephalitis. The reported incidence of anti-LGI1 is 0.83/million/year, with elderly males accounting for the overwhelming majority of cases. While anti-LGI1 encephalitis is a well-known cause of autoimmune encephalitis in men over 50, our literature review found no published cases in pregnant women. The purpose of this study is to describe a rare presentation of this pathology in an unexpected population. Case Presentation: A 21-year-old gravida 2, para 1001 woman at 20 weeks’ gestation presented with worsening seizure-like activity for the past four months, frequent falls, loss of consciousness, and concern for trauma to the abdomen. Her neurologic workup one month prior revealed a 72 h electroencephalography (EEG) with epileptic seizures of the left frontotemporal region, but a normal magnetic resonance image (MRI) of her head. A repeat MRI during this hospitalization showed bilateral limbic and basal ganglia T2 hyperintensities. She was treated with increasing doses of antiepileptic drugs without improvement and was transferred to a neurology intensive care unit, where she was diagnosed with anti-LGI1 encephalitis. She was initially treated with oral corticosteroids with inadequate response, then with intravenous immunoglobulin therapy (IVIG). Her seizure activity persisted throughout her pregnancy, requiring multiple admissions for IVIG, but she eventually delivered a healthy baby and continues to receive long-term care for her new diagnosis. Conclusions: This case illustrates classic findings of anti-LGI1 encephalitis in a non-classic patient population. Knowledge that such a case exists may serve to broaden the differential diagnoses when physicians are presented with a similar pregnant patient and expand the reported patient population in this rare disease.